A cauliflower-shaped nickel @ porous calcium silicate core-shell composite: Preparation and enhanced electromagnetic shielding performance. (20th October 2020) - Wu, Xiaomei; Wen, Bianying
Abstract: Modifying magnetic metals on the surface of inorganic porous materials can not only impart conductive and magnetic ability to inorganic insulating materials, but also make full use of the rich porous structure of porous materials to absorb and consume electromagnetic energy when electromagnetic waves are incident. In this work, a cauliflower-shaped nickel-plated porous calcium silicate (Ni@PCS) functional composite with core-shell structure was successfully fabricated via electroless plating. The electromagnetic shielding performance of the prepared Ni@PCS was investigated and the corresponding electromagnetic shielding mechanism was discussed. Results indicate that the prepared Ni@PCS achieves excellent electromagnetic shielding effectiveness of 58.1 dB at X band with only 0.9 mm of sample thickness. The synergistic effect of multiple energy dissipation is the main electromagnetic shielding mechanism of this core-shell composite. The nickel shell with excellent electrical and magnetic conductivity is responsible for most of the reflection loss and magnetic loss; the interface between the PCS core and the nickel shell produces interfacial polarization loss, while the cauliflower-shaped porous structure provides the internal multiple reflection loss. The results also illustrate that coating magnetic metals on the surface of inorganic porous materials is an effective strategy to prepare high-performance electromagnetic shielding composite materials. Graphical abstract: Image 1